Non-Hodgkin's lymphoma developed during imatinib mesylate treatment of chronic myeloid leukemia. (June 2023) - Kassar, Olfa; Kahla, Aicha Ben; Koubaa, Asma; Kallel, Faten; Amor, Imen Ben; Elloumi, Moez
Introduction: Non-Hodgkin lymphoma induced by imatinib, as a tyrosine kinase inhibitor, is a rare complication. Case report: A 54-year-old female with a history of chronic myeloid leukemia (CML) was treated with imatinib as first-line therapy. The patient achieved a profound molecular response with treatment-free remission after five years but lost major molecular responses. A second deep molecular remission was again achieved. Nine years after imatinib therapy, the patient developed odynophagia and rhinorrhea. Physical examination revealed enlarged tonsils with a tumor-like appearance without palpable lymph nodes. Immunohistochemical examination of the tonsils revealed a large B-cell lymphoma. According to Naranjo's algorithm, the causality relationship with the drug is possible with a score of 3. Management and outcome: Imatinib was discontinued. The lymphoma was treated with rituximab and chemotherapy. Discussion: Non-Hodgkin's lymphoma is a rare side effect of tyrosine kinase inhibitors and highlights the importance of follow-up CML patients.